ISLAM DAN TOLERANSI - Zulham Zulham; Khairuddin Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Tolerance is an attitude of respecting differences and cooperation to achieve a goals within the framework of diversity. Tolerance in Islam is n new, but it already exists and has been exemplified by the prophet Muhammad Saw since ancient times ago. Religious tolerance according to Islam is not to merge in one another’s beliefs, nor is it to exchange beliefs among different religious groups. Tolerance in Islam is in mu’amalah (social interaction), there are certain mutually agreed upon limits that may and may not be violeted. This is the goal of tolerance in which each party has to control himself and provide space to respect each other’s uniqueness without feeling threatened by their beliefs or right. The Al-Quran has guaranteed that there is no compulsion in religion, meanijng that Muslims are not justified in forcing other people to embrace Islam and the prophet taught not to be hostile to people other than Muslims except those who do not respect and insult Islam. Islam has been taught and developed with gentle practices full of tolerance and this has been proven by the glory of Islam for centuries so that the glory of Islam is recorded in he history world civilization until now